Brazilian economic duality and natural gas from Santa Catarina the Prussian Way (PerCursos, 2024)
Based on Marx's and Lenin's understanding of the forms of development, this article presents the foundations of the socio-economic formation of Brazil and Santa Catarina and considerations about Santa Catarina's natural gas distribution infrastructure sector. It uses the Brazilian thinkers Ignacio Rangel (economist) and Armen Mamigonian (geographer) as the main foundations for analyzing the reality of these processes of national and state formation, including the role played by the center of the world economic system that influences Brazilian cycles. The study also includes the historical composition of regional and municipal politics in the state of Santa Catarina and the consequent appointment of leaders to run a public service that operates under a concession system. As a result, it highlights the role of the power pacts articulated between the political and economic classes as a steering unit for development in Brazil after the 1930 Revolution, also having an influence on a strategic infrastructure sector, as in the case of natural gas.
Keywords: Prussian Passage; economic duality; industrialization; natural gas